RENT TO OWN AS VALUE-BASED FINANCIAL INTERMEDIATION: LEGAL AND SHARIAH ANALYSIS - Mohd Zakhiri Md Nor; Ani Munirah Mohamad; Ain Husna Mohd Arshad; Najah Inani Abdul Jalil (Journal of Business Management and Accounting, 2021)
Generally, Rent to Own (RTO) is a financial scheme offered by financial institutions to help those who cannot afford the 10% initial deposit and access to financial schemes. One value-based intermediation (VBI) initiative is the RTO Islamic financing product. The market segment of this product is for the new generation whereby they can own a house without paying any deposit on account of the fact that housing estates are increasingly expensive. This paper starts with the background concept of VBI, then it discusses on the modus operandi of RTO offered by financial institutions. This paper also discusses legal and Shariah aspects related to RTO. Adopting a qualitative method, the data were collected through semi-structured interviews with relevant parties involved with the RTO product. In addition, some preliminary information had been accessed through the financial institutionâ€™s website. This paper found that RTO has played important roles as one viable VBI initiative and it is approved as a Shariah compliant product